On misty island: thomas & friends - Allcroft, Britt; Corby, Jill Davis, Jon (Egmont London, 2012)
In Thomas & Friends: Misty Island, Thomas the Tank Engine embarks on an unexpected adventure when he gets lost on Misty Island while trying to help build a new Sodor Search and Rescue Center. On the mysterious island, Thomas meets unconventional engines named Bash, Dash, and Ferdinand. Together, they face challenges, learn the importance of teamwork, and find a way back to Sodor. The story highlights friendship, problem-solving, and courage.